Effect of delayed implantation on differentiation of the extra-embryonic endoderm in the mouse blastocyst. - Gardner, R; Davies, T; Carey, MS (1988)
Delayed implanting blastocysts recovered from both ovariectomized and lactating pregnant mice were examined for the presence of primitive endoderm. One or more of three different criteria were used to identify this tissue which was found to be present in nearly all such blastocysts, regardless of the length of time for which their implantation had been delayed. Furthermore, the tissue appeared to differentiate in blastocysts from ovariectomized females at approximately the same postcoital stage as in those from sham-operated controls. Formation of the parietal endoderm layer was not observed in a single instance during delay, but began approximately 10 h after it had been terminated by injecting ovariectomized females with oestradiol benzoate. Cells in mitosis were found both at longer intervals after the onset of implantation delay and at shorter intervals after its termination than reported previously. It is concluded that, contrary to what might have been anticipated from certain earlier studies, there seem to be no obvious advantages in using delayed implanting rather than nondelayed blastocysts for investigating initial steps in differentiation of the primitive endoderm. Delayed blastocysts may, nevertheless, be of value in elucidating factors controlling the differentiation or onset of migration of parietal endoderm cells.